Clinical efficacy of weight loss herbal intervention therapy and lifestyle modifications on obesity and its association with distinct gut microbiome: A randomized double-blind phase 2 study - Cao, Ming-Zhuo; Wei, Chun-Hua; Wen, Ming-Chun; Song, Ying; Srivastava, Kamal; Yang, Nan; Shi, Yan-Mei; Miao, Mingsan; Chung, Danna; Li, Xiu-Min (Frontiers in Endocrinology, 2023)
Goals: To assess the efficacy and safety of Chinese Medicine Prescription “W-LHIT” in subjects with simple obesity, and to explore its potential mechanism of action. Methods: Thirty-seven patients aged 18 to 60 from Wei-En hospital (Weifang City, Shandong, China), participated in a double blinded, placebo-controlled study. Subjects were randomly divided into 2 groups, 18 in treatment and 19 in placebo group. The treatment group took the “W-LHIT” capsules for two months, while the control group received placebo capsules. Both groups accepted healthy lifestyle education materials. After a 2-month treatment, the placebo group transferred to open-label treatment after unblinding. Results: 72.22 % participants in the treatment group lost more than 5% of their body weight, compared with 36.84% in the placebo group. Body weight, body mass index, and hip circumference were also significantly lower in the treatment group than in the placebo group (p = 0.06, p < 0.05 and p = 0.09). These changes were accompanied by increased abundance of Akkermansia muciniphila and Enterococcus faecium, and decreased abundance of endotoxin bearing Proteobacteria in gut microbiota. Furthermore, the treatment group also showed improvement in obesity-related comorbidities such as hypertension and elevation of liver enzyme. No serious adverse reactions were found during the study period. Weight did not rebound at a follow-up visit 2 months after treatment. Conclusion: W-LHIT significantly improved body weight and comorbid conditions without obvious adverse reaction or rebound weight gain. These effects were associated with increased abundance of probiotics in gut microbiota. W-LHIT may have a potential for treating obesity in conjunction with healthy lifestyle modifications.